E-wallet usage: a survey among smartphone users in UiTM Puncak Perdana / Nur Azila Md Yusof, Farrah Diana Saiful Bahry and Mohd Ridwan Seman @ Kamarulzaman - Md Yusof, Nur Azila; Saiful Bahry, Farrah Diana; Seman @ Kamarulzaman, Mohd Ridwan (Faculty of Information Management, 2022)
The study aims to determine the usage of e-wallet among smartphone users in UiTM Puncak Perdana. The potential to make electronic payment transaction to purchasing goods is more convenient for users has increased day by day. Since the pandemic era, this approach has encouraged users to use it more. Moreover, the research findings can help service provider to determine whether users fully utilize e-wallet even after MCO completed. An exploratory study involving surveys with self-administered questionnaires was conducted among 103 of smartphone users in UiTM Puncak Perdana from November 2021 until January 2022. The respondents comprised Students, Academic Staff, Administrative Staff, and others. Descriptive analysis was used to present the findings. The findings shows that Social Influence and Facilitating Condition were fully supported. Recommendations are proposed to expend sample size and conducting more studies in e-wallet.